From Corrosion to Collapse: Spatiotemporal Evolution of Local Stability in Anchored Anti-Dip Slopes - Wang, Ding-Jian; Wang, Qian-Yun; Fan, Zhi-Qiang; Ouyang, Fang; Zhang, Ya-Hui (Civil Engineering Journal, 2026)
The long-term stability of anchored anti-dip slopes in hydropower and mining projects is threatened by corrosion-induced degradation of rock bolt systems. Existing deterministic models relying on global safety factors fail to capture localized failure mechanisms and inherent geotechnical uncertainties. This study aims to develop a probabilistic framework for assessing the spatiotemporal stability evolution of such slopes under progressive bolt corrosion. A novel Factor of Local Safety (FoLS) is introduced to quantify stability at individual rock column levels, enabling spatially explicit assessment. This metric is integrated with a time-variant mechanical model for bolt capacity loss and Monte Carlo simulation for uncertainty propagation. Applied to a representative slope, the framework reveals complex degradation patterns: failure initiates in the extremely active toppling zone, progresses to the moderately active zone, and ultimately extends to the passive and shear sliding zones. Sensitivity analyses highlight the critical influence of bolt inclination, yield strength, bolt-rock bond strength, and grout water-cement ratio. Comparative anchorage scenarios demonstrate the superior long-term effectiveness of lower-bench reinforcement. The study provides a novel, spatially differentiated approach for the design, maintenance, and risk management of anchored anti-dip slopes, emphasizing the necessity of dynamic stability monitoring over time.